2005
DOI: 10.1124/jpet.105.091017
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor and Vasodilator Effects of Adenosine in the Mouse Kidney due to Preferential Activation of A1 or A2 Adenosine Receptors

Abstract: The present experiments in mice were performed to determine the steady-state effects of exogenous adenosine on the vascular resistance of the whole kidney, of superficial blood vessels, and of afferent arterioles. The steady-state effect of an intravenous infusion of adenosine (5, 10, and 20 g/min) in wild-type mice was vasodilatation as evidenced by significant reductions of renal and superficial vascular resistance. Resistance decreases were augmented in adenosine 1 receptor -nitro-L-arginine methyl ester (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 35 publications
1
60
0
1
Order By: Relevance
“…In contrast, selective augmentation of adenosine around afferent arterioles causes persistent vasoconstriction, involving Adora1a. Thus, adenosine is a renal constrictor only when it can interact with afferent arteriolar Adora1a without affecting the bulk of renal Adora2a at the same time (61). Other studies have shown that ENT inhibition with dipyridamole is associated with an initial constriction of the afferent and efferent arterioles at an early phase and subsequent dilation at a later phase, with the same degree of vasoconstrictive and vasodilatory effect on both arterioles in rats (62).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, selective augmentation of adenosine around afferent arterioles causes persistent vasoconstriction, involving Adora1a. Thus, adenosine is a renal constrictor only when it can interact with afferent arteriolar Adora1a without affecting the bulk of renal Adora2a at the same time (61). Other studies have shown that ENT inhibition with dipyridamole is associated with an initial constriction of the afferent and efferent arterioles at an early phase and subsequent dilation at a later phase, with the same degree of vasoconstrictive and vasodilatory effect on both arterioles in rats (62).…”
Section: Discussionmentioning
confidence: 97%
“…With regard to adenosineinduced renal vasodilation, a study using an isolatedperfused hydronephrotic rat kidney preparation showed that adenosine-induced dilation of afferent arterioles was mediated by adenosine A 2a receptor-dependent activation of K ATP channels (327). A recent study in mice using intravenous infusion of adenosine indicated that the resulting renal vasodilation is due to adenosine A 2a receptor-mediated activation of endothelial NO synthase (109). Whether the same pathway contributes to medullary vasodilation in response to endogenous adenosine, which probably derives from the abluminal site, remains to be determined.…”
Section: Mechanisms Of Adenosine-mediated Vasoconstriction and Vasmentioning
confidence: 99%
“…##P Ͻ 0.01 vs. single treatment at renal perfusion pressure of 100 mmHg. receptors play important modulatory roles in regulating renal afferent arteriolar tone, and activation of A 2 receptors offsets the counteracting influence of A 1 receptors resulting in vasodilation (10,18,27,35,36,38,41). However, previous studies regarding the function of the A 2 receptors have been focused primarily on A 2A subtype, with the effects of A 2B receptors given less attention.…”
Section: Discussionmentioning
confidence: 93%
“…As the concentration of adenosine increases, the vasodilatory stimulus become predominant (10,18,27,35,36,38,41). Activation of adenosine A 1 receptors in the renal vasculature results in vasoconstriction that reduces the glomerular filtration rate (30, 32) and renal blood flow (4), enhances tubuloglomerular feedback responses (37), and inhibits renin secretion (38).…”
mentioning
confidence: 99%